Food Macromolecules and Colloids - Dickinson, E.; Lorient, Denis (Cambridge : Royal Society of Chemistry, 1995)
Annotation Food macromolecules play a crucial role in the formulation of a wide range of food products such as beverages, bread, cheese, dressings, desserts, ice-cream, and spreads. This book presents the very latest research in the area and is unique in covering both proteins and polysaccharides in the same volume. Specifically it describes recent experimental and theoretical macromolecules in solutions, suspensions, gels, glasses, emulsions and foams. Food Macromolecules and Colloids takes a fundamental approach to complex systems, providing an understanding of the physico-chemical role of macromolecular interactions in controlling the behaviour of real and model food colloids. It gives special attention to adsorbed protein layers, the stability of emulsions and foams, and the viscoelasticity and phase behaviour of mixed polysaccharide systems, as well as to the rheology and microstructure of biopolymer gels, and the interaction of proteins with lipids and aroma compounds. This attractive, typeset publication gives exceptionally broad international coverage of the subject and will make interesting reading for postgraduates, lecturers and researchers with interests in food science, surface and colloid science and polymer science.
Includes bibliographical references and index.
Keywords: Food -- Composition; Macromolecules